Salivary Melatonin and the Severity of Attachment Loss: A Case-Control Study. (9th June 2014) - Golpasand-Hagh, Leila; Zakavi, Faramarz; Daraeighadikolaei, Arash; Ahangarpour, Akram; Hajati, Sara; Daraeighadikolaei, Arsham
Abstract : Background . Melatonin (MT: N-acetyl-5-methoxytryptamine) is a neuroendocrine hormone secreted mainly by the pineal gland in the brain. MT is produced with a circadian rhythm characterized by elevated blood levels during the night. In healthy individuals, maximal secretion of MT occurs between midnight and 2:00 am, whereas the minimal production occurs during the day. MT can be determined by repeated measurement of plasma or salivary MT or urine sulfatoxy-melatonin. Melatonin has powerful antioxidant effects, has an immunomodulatory role, stimulates the synthesis of type I collagen fibers, and promotes bone formation. Melatonin is also secreted in the saliva, although its role in the mouth is not known well. The purpose of this study was to examine the correlation between salivary melatonin level and periodontal diseases. Methods . Fifty subjects by mean age of40.44 ± 6.38 years were equally divided into 5 groups: 10 healthy subjects, 10 subjects with gingivitis, 10 subjects with localized moderate chronic periodontitis, 10 subjects with generalized moderate chronic periodontitis, and 10 subjects with generalized severe chronic periodontitis. Saliva samples were collected from all the subjects and melatonin levels were determined using an enzyme-linked immunosorbent assay. Two-way and one-way ANOVA and Tukey test were used to analyze relationships among variables. Results . Healthy subjects had significantly higher salivary melatonin level (5.29 ± 0.50 pg/mL) compared to patients with gingivitis (4.35 ± 0.30 pg/mL) (P < 0.001 ). The difference between salivary melatonin level in patients with gingivitis and periodontitis was significant (P < 0.001 ). Level of melatonin in patients with generalized severe chronic periodontitis (3.39 ± 0.10 pg/mL) was significantly lower than that in other groups (P < 0.01 ). Conclusions . This study determined that salivary melatonin level in patients with periodontal diseases is lower than that in healthy subjects. Consequently we conclude that there is a negative correlation between melatonin level and the severity of disease, suggesting that melatonin might have a protective role against periodontal diseases, although further research is required to validate this hypothesis.